Fluorescent Chemosensors for Ion and Molecule Recognition: The Next Chapter - Yan, Kai-Cheng; Steinbrueck, Axel; Sedgwick, Adam C.; James, Tony D. (Frontiers in Sensors, 2021)
Over the past 30 years fluorescent chemosenors have evolved to incorporate many optical-based modalities and strategies. With this perspective we highlight the current state of the art and the future challenges remaining in the area. In order to facilitate the readers understanding of the area we provide appropriate contemporary examples. We then conclude with our thoughts on the most probably direction chemosensor development will take in not too distant future.